(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical characteristics and evaluate the outcomes of care and treatment for chronic non-healing ulcers in patients with diabetes mellitus using negative pressure wound therapy. Methods: A descriptive case-series study with a pre-post intervention comparison was conducted among 40 patients with diabetes mellitus presenting with grade III-IV chronic non-healing ulcers according to the EPUAP classification, treated with negative pressure wound therapy from April to December 2023. Clinical parameters, including ulcer area, exudate, wound bed condition, and pain severity and characteristics, were assessed before treatment and after 3, 5, and 8 days of treatment. Data were analyzed using SPSS version 20. Results: Most patients were older than 65 years (67.5%) and had poor glycemic control (HbA1c ≥ 7% in 97.5%). After 8 days of treatment, 100% of ulcers had an area < 30 cm², exudate was markedly reduced, 97.5% achieved a healthy wound bed, and 85% reported no pain or only mild pain. Granulation tissue coverage ≥ 75% was achieved in 60% of cases (p < 0.01). The overall treatment success rate was 80%. Advanced age, stump ulcer location, large ulcer size, heavy exudate, and severe pain were associated with treatment failure (p < 0.05). Conclusion: Negative pressure wound therapy demonstrates clear effectiveness in the treatment of chronic non-healing ulcers in patients with diabetes mellitus, contributing to rapid improvement in clinical characteristics, pain reduction, and increased wound healing rates.